A High Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS) Qualitative Detection Method Developed for In Vivo Analyses of Toxin Orellanine from the Cortinarius orellanus Fr.—Part II. (7th February 2012) - Brondz, Ilia; Brondz, Anton
Abstract : The high-performance liquid chromatography—mass spectrometry (HPLC-MS) qualitative analysis method in negative mode of detection was used to record the presence of orellanine in the stomach contents of rats after ingestion of Cortinarius orellanus . Intoxication with orellanine causes acute renal failure (ARF), which is characterized by sudden loss of the ability of the kidneys to excrete wastes. The detection method presented here can be used as a platform for future development of analytical procedures for detecting orellanine in cases of human intoxication by toadstools. The presence of orellanine in animal stomach contents was analytically recorded and compared with standard orellanine, which was donated by the R&D Department of Jupiter Ltd, Norway. The MS fragmentation described in the literature and the MS fragmentation of standard samples of isolated orellanine verified the presence of orellanine in the stomach contents of laboratory animals. The presence of a diglucoside of orellanine, which was described as part of the toxic orellanine complex by Spiteller et al., in the stomach contents of animals, was also verified using HPLC-MS.